A Taxonomy of Critical Dimensions at the Intersection of Learning Analytics and Educational Measurement - Scalise, Kathleen; Wilson, Mark; Gochyyev, Perman (Frontiers in Education, 2021)
From a measurement perspective, a variety of analytic approaches are fast emerging in the data mining and exploratory analytics branches of the field of data sciences. In particular, for learning analytics, more theory is needed showing how the analytical approaches are related to one another and to their respective purposes when measurement is involved. For example, machine learning acting on process data can yield sets of specific patterns as results, but the critical question from a measurement perspective is: What do these results mean and how can they be used successfully in learning analytics? That is, if the goal is to make an inference regarding some underlying variable or set of elements about a student (or a teacher, school, or other agent or program within an educational setting), what claims are being made regarding the evidence and how can learning analytics contribute? In this paper we introduce techniques that move toward theory extensions that need to be developed at the intersection of learning analytics with measurement technology. For elucidating potential theoretical components from a measurement perspective, we draw on a type of case study research in the computer science domain, specifically employing “use cases.” A use case in computer science describes a scenario of use for software. Different use cases can describe different situations in which software may have utility. Like other multi-case designs, use cases can offer a means of exploring relationships and advancing potential theories by comparing similarities and differences among the cases. Here we explore three LA use case examples that differ purposively in critical ways. Examining their similarities and differences highlights potential dimensions that distinguish among emerging LA use cases at the intersection of data science and measurement technology.